2022
DOI: 10.3390/nano12060983
|View full text |Cite
|
Sign up to set email alerts
|

CoFeS2@CoS2 Nanocubes Entangled with CNT for Efficient Bifunctional Performance for Oxygen Evolution and Oxygen Reduction Reactions

Abstract: Exploring bifunctional electrocatalysts to lower the activation energy barriers for sluggish electrochemical reactions for both the oxygen evolution reaction (OER) and oxygen reduction reaction (ORR) are of great importance in achieving lower energy consumption and higher conversion efficiency for future energy conversion and storage system. Despite the excellent performance of precious metal-based electrocatalysts for OER and ORR, their high cost and scarcity hamper their large-scale industrial application. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Wang's group has recently reported that the core-shell structure of Au@NiCo 2 S 4 core-shell NPs could result in a higher proportion of high-valance Ni/Co cations and improve its electronic conductivity, which collectively enhances its OER catalytic performance [20]. In addition, a great number of the heterostructures have also been fabricated for an improved electronical performance, such as CoP/FeP 4 [21], Co 9 S 8 /CoO/NC [22], CoFeS 2 @CoS 2 [23], Ni-P-S@FeOOH/CC [24], Ni 5 P 4 /Ni 2 P-FeNi [25], and MnO-OVs/NCNTs [26].…”
Section: Introductionmentioning
confidence: 99%
“…Wang's group has recently reported that the core-shell structure of Au@NiCo 2 S 4 core-shell NPs could result in a higher proportion of high-valance Ni/Co cations and improve its electronic conductivity, which collectively enhances its OER catalytic performance [20]. In addition, a great number of the heterostructures have also been fabricated for an improved electronical performance, such as CoP/FeP 4 [21], Co 9 S 8 /CoO/NC [22], CoFeS 2 @CoS 2 [23], Ni-P-S@FeOOH/CC [24], Ni 5 P 4 /Ni 2 P-FeNi [25], and MnO-OVs/NCNTs [26].…”
Section: Introductionmentioning
confidence: 99%
“…Changing the specific surface area and the surface interface properties of catalysts can affect their catalytic properties; hence, the structure of the materials can be reasonably designed and regulated to obtain the desired catalytic properties. The synthesis methods of the catalysts are mainly divided into thermal decomposition, electrodeposition, and electrospinning [ 85 , 86 ]. During OER/ORR, the adsorption energy of the oxygen intermediates depends on the surface geometry.…”
Section: Synthetic Methodsmentioning
confidence: 99%
“…Whereas the peak corresponding to sulfur-oxygen bonding at the binding energy of 169.5 eV has become significant, inferring the oxidation of sulfur during the water oxidation process, which is quite sensible to observe in catalysts like CFTS and has been reported similarly in related reports. 70,71 Moreover, the oxidation of transition metal sulfides upon the long-term OER reaction under strong alkaline conditions is investigated in detail and has been reported to be thermodynamically unavoidable by Han et al 71 Furthermore, a partial oxidation process occurs during the long-term OER, resulting in the formation of an amorphous oxide layer on the electrocatalyst, which is beneficial for the adsorption and desorption of OH and H atoms, ensuring undeteriorated performance even after the long-term OER reaction. 71 However, the XRD pattern of EG-CFTS after the AOR test for 20 h revealed that there was no significant change in the crystal phase (Fig.…”
Section: Aor Electrocatalytic Activity Of Cfts Nanosheet Arraysmentioning
confidence: 99%